Bridging the gap between tracking and detecting changes in XML. (8th December 2014) - Ciancarini, Paolo; Iorio, Angelo Di; Marchetti, Carlo; Schirinzi, Michele; Vitali, Fabio
Summary: There are two main approaches to manage changes in XML documents, change‐tracking and diff. Change‐tracking tools, which record edit actions while they are performed on the source document, are able to capture the exact editing process. That is much more difficult for diff algorithms, which have to reconstruct it by comparing two different versions. Interestingly, these algorithms process both text‐centric and data‐centric XML documents the same way. In this paper, we show that more accurate, clear, and human‐readable results can be achieved on text‐centric resources, by employing specific models and algorithms. We describe and discuss a specialized diff algorithm for such a class of documents. We also compare a Java implementation of the algorithm, named JNDiff, with other general‐purpose or data‐oriented diff tools, focusing on the quality of their output. Copyright © 2014 Copyright © 2014 John Wiley & Sons, Ltd.